PENGARUH PEMAKAIAN GAS OKSIGEN PADA TAHAP PEMBUATAN MATERIAL Ba-Ca-Cu-O[Effect of Oxygen Gas Usage at the Preparation Stage of Ba-Ca-Cu-O Material] - Imaduddin, Agung; Firdiyono, Florentinus; Sebleku, Pius; Suryantoro, Anton; Lestari, Franciska Pramuji (Jurnal Metalurgi, 2013)
Since the discovery of Copper-oxide superconductors in 1986 which having a high critical temperature (TC), the world’s attention is increasingly focused on these materials to find superconductors with even higher TC. Hg-based superconductors are superconductors with highest TCvalue among other types. In this work, we has prepared precursor by mixing BaCO3, CaCO3 and CuO powder manually. , And then heated in the furnace at temperatures of 900 C and 930 C for 12 hours with the use of variable oxygen gas and air flow. Regarding to the analysis of XRD (X-Ray Diffractometer), we obtained BaCuO2 compounds, and also based on analysis of FWHM (Full Width at Half Maximum) at its highest peak and the results of EDS analysis, it was known that heating at temperatures of 930 C and the using of oxygen gas optimizes the reaction formation of BaCuO2 and improvesthe crystallization of BaCuO2 compounds.